Formação continuada em educação física e inclusão do deficiente no ensino regular sob a ótica de professores =: The ongoing graduation in physical education studies and the inclusion of disable people in regular schools under the teacher's perception - Tebaldi, Marina [UNESP] (2014)
This current investigation focuses on analyzing municipal school teachers’ perception in Rio Claro city, State of São Paulo. It concerns the continuing education in Physical Education studies and the inclusion of disabled students in regular schools. It is about qualitative research and in the literature review, issues referred to continuing education, inclusion and inclusive education have been approached. Through semi structured interviews, four declarations have been given by municipal school teachers in Rio Claro/SP and another one was given by the teaching coordinator of Special Education. The information collected in the interviews has been analyzed through Content Analysis Technique. Favorable declarations regarding ongoing graduation contributions in inclusive perspective have been verified. They have supported teachers in the difficult pedagogic task referred to disabled students’ inclusion in Regular Education. Nevertheless, multidisciplinary work is not performed yet and there is lack of materials and resources, in other words, there is lack of adequate physical facilities. Besides the Public Policy Programs offered by the City Hall to municipal teachers, it is necessary to provide courses with emphasis on inclusive themes such as specific ones regarding scientific terms and the pedagogical intervention in the field of intellectual and motor disabilities. Otherwise, what is determined by laws as well as approached by experts in this field will be hardly corresponded. It was concluded that for inclusive continuing education for teachers to be effective, there must be a multidisciplinary work, meeting all the needs of the students, an ongoing education designed by teachers, and performed with the aid of the same